PENYULUHAN DAN TRAINING PENYUSUNAN ANGGARAN DEMI PENINGKATAN SKILL NETRA PERTUNI BALI - Putri Prawitasari, Putu; Intan Puspadewi, Anak Agung Ayu; Ari Kesuma Dewi, Ni Ketut; Sariani, Ni Luh Putu (Universitas Pahlawan Tuanku Tambusai, 2023)
Pertuni Bali is one of the organizations that brings together the blind in Bali with various activities that require activity proposals and budget preparation. The findings of the community service team show that there are errors and a lack of literacy of the Blind in making activity proposals, especially in budget preparation. This prompted a team of lecturers from the National Education University to provide counseling and training on budget preparation using 2 methods, namely the first day 8 October 2023 with public education, namely through counseling regarding making activity proposals, especially procedures for making activity proposal budgets. On the second day, October 22 2023, training methods were carried out with demonstrations and group budget preparation exercises. In this method, we carry out intensive discussions to produce additional skills for the Pertuni Bali blind group. The results of the service showed an increase in pretest results from 45% to 91% and the results of discussions and case presentations showed improvement. This indicates the success of improving Netra Pertuni Bali's skills in budget preparation.